Role of morphologic characteristics of the uterine septum in the prediction and prevention of abnormal healing outcomes after hysteroscopic metroplasty - Ludwin, A. (Oxford University Press, 2014)
STUDY QUESTION: Can morphologic measurements (width, length and surface area) of the uterine septum predict healing-dependent abnormal anatomic results [ARs; residual septum (RS) and intrauterine adhesions in other locations (IUA-OLs)] after complete hysteroscopic metroplasty (HM)? SUMMARY ANSWER: Significant predictors of ARs are the septal width and, to a lesser extent, septal surface area. WHAT IS KNOWN ALREADY: Anatomic results after hysteroscopic metroplasty have very large variation. A RS >1 cm and IUA-OLs can aggravate reproductive outcomes, resulting in the need for reoperation. New criteria for diagnosing a uterine septum according to the European Society of Human Reproduction and Embryology (ESHRE) and European Society for Gynaecological Endoscopy (ESGE) have been suggested (ESHRE-ESGE criteria). Autocross-linked hyaluronic acid gel (autocross-linked polysaccharide) has an antiadhesive effect. STUDY DESIGN, SIZE, DURATION: A prospective, observational cohort study was performed with 96 women consecutively enrolled between 2007 and 2012. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women who had uterine septum and previous miscarriage or infertility presented for evaluation at a university hospital, private hospital or private medical center were included. Preoperative septal width, length and surface area were determined with three-dimensional sonohysterography. Women were treated by hysteroscopy in a standardized manner with three- or four-dimensional transrectal ultrasound guidance (complete resection). Patients received either no adhesion barrier (49 patients) or adhesion barrier with autocross-linked polysaccharide (47 patients). Anatomic results were assessed with three-dimensional sonohysterography and second-look hysteroscopy. Healing-dependent ARs were reported using both American Society of Reproductive Medicine (ASRM) criterion of RS length >1 cm (ASRM>1 cm criterion) and ESHRE-ESGE criteria. Univariate and multivariate logistic regression were used to identify predictors of RS, IUA-OLs and ARs. MAIN RESULTS AND ROLE OF CHANCE: In patients who had no adhesion barrier, ARs were diagnosed in 11 of 49 patients (23%) using the ASRM > 1 cm criterion and in 20 of 49 patients (41%) using the ESHRE-ESGE criteria for RS [odds ratio (OR)(ESHRE-ESGE:ASRM), 2.4, P = 0.05]. In the patients who had autocross-linked polysaccharide, ARs(ASRM) (>) (1 cm) were diagnosed in 2 of 47 patients (4%) and ARs(ESHRE-ESGE) in 4 of 47 patients (9%). RS(ESHRE-ESGE) was diagnosed significantly more often than RS(ASRM) (>) (1 cm) 19 of 96 (20%) versus 5 of 96 (5%) in all patients (OR(ESHRE-ESGE:ASRM) (>) (1 cm) = 4.5, P < 0.01). In patients who had no adhesion barrier, logistic regression with ASRM > 1 cm and ESHRE-ESGE criteria showed that the width and surface area were predictors of ARs. Models adjusted by patient group confirmed the significance of width as a predictor of ARs(ASRM) (>) (1 cm) [OR for width, 3.5 (P < 0.01); OR for group, 0.22 (P < 0.01)], width as a predictor of ARs(ESHRE-ESGE) [OR for width, 2.2 (P < 0.01); OR for group, 0.26 (P < 0.01)] and surface area as a predictor of ARs(ASRM) (>) (1 cm) [OR for surface area, 1.5 (P < 0.01)]; OR for group, 0.32 (P < 0.01). In patients who had autocross-linked polysaccharide, these predictors were not significant. Receiver-operating characteristic curves showed cutoff values for ARs(ASRM) (>) (1 cm) (septal width, 3.42 cm; septal surface area, 4.68cm(2)) and ARs(ESHRE-ESGE) (septal width, 3.42 cm; septal surface area, 3.51cm(2)). LIMITATIONS AND REASONS FOR CAUTION: Patients were enrolled in the adhesion barrier group in a time-dependent, consecutive and non-randomized manner. WIDER IMPLICATIONS OF THE FINDINGS: A wide septum and large surface area may be indications for adhesion barrier. The use of autocross-linked polysaccharide reduces the risk of ARs. The ESHRE-ESGE criteria may cause greater frequency of recognition of RS than the ASRM > 1 cm criterion, which could result in more frequent reoperations with use of the ESHRE-ESGE criteria, possibly without any significant effect on reproductive performance. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by Jagiellonian University (grant no. K/ZDS/003821). The authors have no competing interest to declare.